Participatory Marketing of Pop Culture on X - Jasmine Alya Pramesthi (Universitas Telkom, 2025)
This study explores the phenomenon of public-driven promotion through the hashtag #NontonJumboLagi, which emerged organically on Twitter/X and played a pivotal role in boosting the Indonesian animated film Jumbo to the top of the national box office. The research aimed to examine how audiences functioned as informal promoters by generating digital discourse that mobilized collective action, emotional attachment, humor, competition, and offline practices. Using a qualitative approach and digital discourse analysis, data were collected from purposively sampled posts that explicitly used the hashtag and represented key categories such as calls to rewatch, expressions of affection, competitive narratives, humor, and community practices. A total of 42 posts were analyzed through open thematic coding, complemented by informal pre-research interviews with active users. The findings reveal that audiences repurposed social media content into organic promotional messages that extended beyond individual expression to collective identity, nostalgia, and cultural pride. These practices formed a participatory and affective word-of-mouth ecosystem that bridged online and offline activities. The study concludes that participatory marketing of popular culture represents a shift in promotional dynamics, where audiences themselves become cultural marketers, redefining how films gain visibility and legitimacy in the digital era.